On–off pulsed oral drug-delivery systems: a possible tool for drug delivery in chronotherapy. (September 2011) - Tran, Thanh Huyen; Lee, Beom-Jin
Circadian rhythms regulate most body functions and are important factors to consider when administering drugs. The existence of circadian rhythms in nature and their influences on human biological systems have given rise to the concept of chronotherapy, which is the science of delivering drugs in a synchronized manner with the rhythm-dependent circadian variation inherent in the human body. The safety and efficacy of a drug can be improved by matching the peak plasma concentration during a 24 h period of the rhythms. An on–off pulsed (pulsatile or time-controlled) release drug-delivery system offers rapid and transient release; stepwise release; and the sustained release of a certain amount of drug within a short time period after a predetermined off-release period according to the circadian rhythm of disease states. These systems deliver the drug at the right time and at an appropriate dosage and are the best approach for chronotherapy. These systems show promise for the optimal therapy of chronic diseases such as asthma, hypertension, myocardial infarction and arthritis, which show a circadian dependency. Various technologies have been adopted to mimic circadian rhythms in physiological functions and diseases. This review focuses on the basic concept of circadian rhythm, chronotherapy and recent advances in the development of on–off pulsed oral drug-delivery systems for optimal therapy.